Plastic padding for the production of corn (Zea mays L.) forage in the Comarca Lagunera - Montemayor Trejo, José Alfredo; Suárez González, Edith; Munguía López, Juan Plutarco; Segura Castruita, Miguel Ángel; Mendoza Villarreal, Rosalinda; Woo Reza, José Luis (Revista Mexicana de Ciencias Agrícolas, 2018)
In the Comarca Lagunera that includes part of the states of Coahuila and Durango, Mexico. The main dairy basin of the country is located. Therefore, the establishment of forage crops exerts the greatest pressure for the exploitation of water resources in this region. The above, generates the constant need to adapt and modify the current production systems. The objective of this research was to evaluate the production of fodder maize through the use of quilted plastics in a belt irrigation system. Three colors of quilting were evaluated: white, silver, black and as a control the soil without quilting in a block design with arrangement in strips. The work was developed in the small property Esmeralda in the municipality of Gomez Palacio, Durango. In the spring-summer cycle of 2012. The variables evaluated were: plant height, stem diameter, diameter and length of corn, fresh and dry weight of the plant and leaf area index (IAF). The results obtained show that there was no significant difference (p≤ 0.05) between the colors of padding for the production of dry matter, but there was difference with respect to the soil without quilting. An IAF growth model was obtained as a function of the days after sowing quadratic type Yca= -0.002X2 + 0.294X -5.8183, R2= 0.97 para acolchado and Ysa= -0.0017X2 + 0.259X -5.503, R2= 0.94 without quilting and a dry matter production model based on the IAF linear type Yca= 86.295X -110.84, R2= 0.92 and Ysa= 65.761X -55.764, R2= 0.91 both for the system with and without padding. It is concluded that the use of plastic mulches for the production of fodder maize increased the yields up to 25% more with respect to the system without quilting.